Dyeing of Polyester and Polyamide Synthetic Fabrics with Natural Dyes Using Ecofriendly Technique. (24th November 2014) - Elnagar, Khaled; Abou Elmaaty, Tarek; Raouf, Sally
Abstract : This work presents an ecofriendly method for dyeing synthetic fabrics with natural dyes using UV/ozone pretreatment to activate fiber and improve dyeability of polyester and nylon. Fabrics are pretreated with UV/ozone for different periods of time ranged from 5 min to 120 min. Effect of pretreatment on surface morphology was studied by scanning electron microscope (SEM). Mechanical behavior was studied by testing tensile strength and elongation percentage. Chemical modification of the surface was studied using attenuated total reflection Fourier transform infrared spectrometer (ATR-FTIR). Dyeability of the treated samples was investigated in terms of their colour strength expressed as K/s in addition to fastness to washing and light. This research showed the increment of the affinity of the studied synthetic fabrics towards curcumin and saffron natural dyes using ecofriendly technique.